2018
DOI: 10.1021/acsphotonics.8b00010
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of Two-Photon Absorption in Layered Transition Metal Dichalcogenides: Experiment and Theory

Abstract: The saturation of two-photon absorption (TPA) in four types of layered transition metal dichalcogenides (TMDCs) (MoS 2 , WS 2 , MoSe 2 , WSe 2 ) was systemically studied both experimentally and theoretically. It was demonstrated that the TPA coefficient is decreased when either the incident pulse intensity or the thickness of the TMDC nanofilms increases, while TPA saturation intensity has the opposite behavior, under the excitation of 1.2 eV photons with a pulse width of 350 fs. A three-level excitonic dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 48 publications
4
60
0
2
Order By: Relevance
“…The TPA coefficient decreases with increasing layer numbers ( Figure 3D). TPA saturation was also reported in four types of TMDs ((MoS 2 , WS 2 , MoSe 2 , and WSe 2 ) with the saturation intensity at the order of 10 2 GW/cm 2 , 141 which was important in the short pulse laser generation. Figure 3E shows a typical TPA saturation of monolayer MoS 2 .…”
Section: Two-photon Absorptionmentioning
confidence: 79%
See 1 more Smart Citation
“…The TPA coefficient decreases with increasing layer numbers ( Figure 3D). TPA saturation was also reported in four types of TMDs ((MoS 2 , WS 2 , MoSe 2 , and WSe 2 ) with the saturation intensity at the order of 10 2 GW/cm 2 , 141 which was important in the short pulse laser generation. Figure 3E shows a typical TPA saturation of monolayer MoS 2 .…”
Section: Two-photon Absorptionmentioning
confidence: 79%
“…Figure E shows a typical TPA saturation of monolayer MoS 2 . The simulation revealed that the significant TPA saturation was originated from the exciton‐exciton annihilation, depletion of electrons in the ground state, and the fast relaxation of the dark excitonic states …”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
“…The saturable absorption and multiple‐photon absorption are two kinds of nonlinear absorption. It is worth noting that if the laser intensity is very high, multi‐photon absorption becomes very important . If two‐photon absorption is considered, the saturable absorption formula can be derived from α=α ns +αS1+I/I sat +βI…”
Section: Fundamental Of 2d Layered Materialsmentioning
confidence: 99%
“…Beyond the linear optical regime, extensive efforts in recent years have been devoted to investigating nonlinear optical responses of TMD monolayers up to the third order. These studies provided valuable information of lattice structure, nonlinear absorption coefficients, fine structures of excitonic levels, and realized subband photodetection, tunable nonlinear optical response, quantum coherence, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the real part of third‐order susceptibility, femtosecond laser THG measurements have been carried out for graphene, MoS 2 , ReS 2 , black phosphorus, etc. In addition, to obtain the imaginary part of third‐order susceptibility, which is proportional to two‐photon absorption (TPA) coefficient, degenerate TPA Z‐scan technique has been used for uniform films of TMDs grown by chemical vapor deposition (CVD) . Z‐scan's simplicity of one‐laser‐beam setup has made it widely employed, while it can suffer from low spatial resolution and limited temporal resolution …”
Section: Introductionmentioning
confidence: 99%